THE CONCEPT OF INCLUSIVE EDUCATION AND UPBRINGING FOR CHILDREN WITH DISABILITIES. - Shaydullayeva Kamola; Avazova Jasmina (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Annotation: This topic highlights the concept of inclusive education and upbringing for children with disabilities. Inclusive education is aimed at providing equal educational opportunities for all children regardless of their physical, intellectual, or emotional characteristics. This concept serves to create a supportive educational environment, apply an individualized approach, ensure social adaptation, and protect the rights and interests of children. Furthermore, the main principles, advantages, and implementation mechanisms of inclusive education are analyzed.